Pengaruh Gaya Kepemimpinan dan Kompetensi terhadap Motivasi yang Berdampak pada Kinerja Pegawai Kantor Badan Narkotik Nasional Kabupaten Tanjung Jabung Timur - Gunawan Gunawan; M. Zahari MS; Osrita Hapsara (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to see how the influence of leadership style and competence on motivation and its impact on employee performance at the BNN office in East Tanjung Jabung Regency, in this study using descriptive and verification research methods. The sample in this study used the census method, namely all employees who were in the BNN office environment, East Tanjung Jabung Regency. The data analysis technique used is path analysis, with the help of the SPSS version 25 software program. The results of this study indicate that the independent variables, namely leadership style and competence, have a positive and significant impact on motivation and a positive and significant impact on performance..